2008
DOI: 10.1097/yco.0b013e3282f3ad89
|View full text |Cite
|
Sign up to set email alerts
|

Social and emotional support and its implication for health

Abstract: PURPOSE OF REVIEW-To summarize recent research findings from selected publications focusing on links between social support and physical health.RECENT FINDINGS-Current research is extending our understanding of social support's influences on health. Many epidemiological studies have concentrated on further linking measures of social support to physical health outcomes. A few studies are now moving into newer areas, such as emphasizing health links to support receipt and provision. Researchers are also interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
462
2
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 683 publications
(524 citation statements)
references
References 41 publications
(35 reference statements)
25
462
2
10
Order By: Relevance
“…Moreover, while some aspects of these patterns are uniquely human, the fundamental link between social connectedness and fitness has a very deep phylogeny, as there is evidence that, among both male and female nonhuman primates, social bonds translate into enhanced survival and reproductive success (Kuhle & Ratdke, 2013;Silk, Alberts, & Altmann, 2003;Silk et al, 2010). Consistent with the above patterns, in the clinical context, social connectedness has been shown to importantly influence both overall human health and prognosis after physical trauma (see Reblin & Uchino, 2008;Seeman, 1996).…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, while some aspects of these patterns are uniquely human, the fundamental link between social connectedness and fitness has a very deep phylogeny, as there is evidence that, among both male and female nonhuman primates, social bonds translate into enhanced survival and reproductive success (Kuhle & Ratdke, 2013;Silk, Alberts, & Altmann, 2003;Silk et al, 2010). Consistent with the above patterns, in the clinical context, social connectedness has been shown to importantly influence both overall human health and prognosis after physical trauma (see Reblin & Uchino, 2008;Seeman, 1996).…”
Section: Introductionmentioning
confidence: 93%
“…It is a transition in life which brings many challenges [1,2], and for this reason, the care and support extended to women can impact greatly on their lives and contribute to how they experience the pregnancy [14]. Social relationships and support, both formal and informal, play critical roles in managing health and personal problems in pregnancy [57].…”
Section: Introductionmentioning
confidence: 99%
“…Social relationships and support, both formal and informal, play critical roles in managing health and personal problems in pregnancy [57]. Reblin and Uchino [2] differentiate between tangible care and support, in the form of money, shelter, clothing, and food, for example; and intangible care and support, including emotional, psychosocial, and perceived or received support. The range of material, contextual, and interpersonal factors that are therefore included reflect the complex phenomena that impact on women [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an extensive review and meta-analysis of 148 papers, it was reported 15 that there is a "50% increased likelihood of survival for those, particularly men, with stronger social relationships" (page 14). In addition, it has been acknowledged that people in later life may conceal "dissatisfaction with conditions that might otherwise be correctable" (page 1111) 3 and that negative life events can be cumulative and can have an increasingly negative impact on quality of life 16,5 and health status 17 .…”
Section: Introductionmentioning
confidence: 99%